Does Strategic Cost Management Matter? Evaluating its Impact on Firm Perfomance - Brigitta Irama Adelya; Gizza Linosa Islamy; Attha Syahira; Ririn Nurilah; Rifani Akbar Sulbahri (Sekolah Menengah Kejuruan (SMK) Pustek, 2026)
Strategic cost management has increasingly attracted attention as firms face rising competition, technological disruption, and pressure to improve efficiency and long-term value creation. Although many studies suggest that Strategic Cost Management (SCM) and Strategic Management Accounting (SMA) contribute to better organizational outcomes, the extent and consistency of their influence on firm performance remain fragmented across the literature. This study aims to systematically examine the relationship between SCM, SMA, and firm performance by synthesizing findings from recent empirical research. The study employs a Systematic Literature Review (SLR) following the PRISMA 2020 guidelines. Articles were collected from the Scopus database covering the period 2016-2026. From an initial identification of 70 publications, 15 empirical studies met the established inclusion criteria and were analyzed using data extraction and comparative synthesis techniques. The review indicates that the implementation of SCM and SMA generally contributes positively to firm performance, particularly through improvements in financial outcomes, operational efficiency, and competitive positioning. However, the strength of this relationship is often influenced by contextual factors such as innovation capability, environmental uncertainty, and the quality of information technology. Overall, the findings highlight the importance of aligning strategic cost management practices with organizational strategy to enhance sustainable firm performance.